Wayward - Spiotta, Dana, 1966- (Alfred A. Knopf, 2021)
"A moving, funny, engrossing novel about mothers and daughters, and one woman's midlife reckoning, from the renowned author of Stone Arabia and Eat the Document. On the heels of the election of 2016, Samantha Raymond's life begins to come apart: her mother is ill, her teenage daughter is increasingly remote, and at 52, she finds herself staring into "the Mids"--that hour of supreme wakefulness between three and four in the morning in which women of a certain age suddenly find themselves contemplating motherhood, mortality, and, in this case, the state of our unraveling nation. When she falls in love with a beautiful, decrepit house in a hardscrabble neighborhood in Syracuse, she buys it on a whim and flees her suburban life--and her family--as she grapples with how to be a wife, a mother, and a daughter, in a country that is coming apart at the seams. Dana Spiotta's Wayward is a stunning novel about aging, about the female body, and about female difficulty--female complexity--in the age of Trump. Probing and provocative, brainy and sensual, it is a testament to our weird, off-kilter America, to reforms and resistance and utopian wishes, and to the beauty of ruins. Tremendous new work from one of the most gifted writers of her generation"--